Mapping hippocampal glutamate in healthy aging with in vivo glutamate-weighted CEST (GluCEST) imaging - Pecsok, Maggie K.; Robinson, Heather; Atkins, Ally; Calkins, Monica E.; Elliott, Mark A.; Mordy, Arianna; Stifelman, Jacquelyn; Gur, Ruben C.; Moberg, Paul J.; Nanga, Ravi Prakash Reddy; Ruparel, Kosha; Shinohara, Russell T.; et al. (Frontiers in Aging Neuroscience, 2025)
IntroductionHippocampal glutamate (Glu) dysfunction is a pertinent indicator of neurodegeneration, yet mapping typical age-related changes in Glu has been challenging. Here, we use a 7T MRI approach, Glutamate Chemical Exchange Saturation Transfer (GluCEST), to measure bilateral hippocampal Glu in healthy old (HOA) and young (HYA) adults.MethodsBilateral hippocampal GluCEST data was acquired from 27 HOA and 22 HYA using 7T MRI. GluCEST differences by age and hemisphere were tested with a linear mixed model. GluCEST asymmetry index was also evaluated by age. Exploratory analyses examined associations between hippocampal GluCEST, age group, and scores on the Montreal Cognitive Assessment (MoCA) and Cognitive Complaints Index (CCI).ResultsGluCEST levels showed an age group and hemisphere interaction. In HOA, GluCEST was higher in left than right hippocampus, but in HYA, GluCEST level was equivalent across hemispheres. HOA had lower GluCEST than HYA in the right hippocampus. GluCEST asymmetry index confirmed significant left asymmetry in HOA. Lower GluCEST levels in HOA were associated with subjective cognitive complaints as measured by the CCI.DiscussionHippocampal GluCEST provides insight into age-related neural changes, with lower GluCEST in the right hippocampus in older adults. These findings offer a step toward elucidating the asymmetrical trajectory of hippocampal glutamatergic alterations and their relationship to cognitive phenotypes.